Comparison of the provision of champedon trunk shell capsule extract and artesunate on placental histopathologic classification in pregnant mice (Mus musculus) malaria model - Achmad Yunus; Budi Prasetyo; Erry Gumilar Dachlan; Aty Widyawaruyanti; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To compare the effect of chemphedon trunk shell capsule extract with artesunate on placental histopathologic classification in pregnant mice malaria’s models.Materials and Methods: This study was a randomized experi-mental laboratory study in BALBc strains mice with controls. A total of 30 pregnant mice were divided into 3 groups. On day 10 each group was infected with P. berghei. Furthermore, on day 11 each group was subjected to thin blood smear examination and subsequent infection when administered antimalarial positive. Group P1 received Chemphedon trunk shell extract 100 mg/kg BW/day per sonde two times per day for 5 days. Group P2 received 36.4 mg artesunate/kg BW/day for 3 days followed by CMC Na per sonde for 2 days, and group P3 received placebo (CMC Na) for 5 days. On day 16 the mice were dissected on 16 days of pregnancy and the placenta was taken and preparations were made to observe histopathological classification of the placenta according to Rogerson. Grouping was performed accor-ding to placental histopathological classification by Rogerson.Results: Groups receiving cemphedon trunk shell capsule extract, artesunate and placebo revealed p=0.004 (p<0.05), showing that there were two groups with significant difference. To determine which group had significant difference, the test was followed by Mann-Whitney post-hoc test. The results showed chempedon trunk shell capsule group and placebo obtained p=0.007 (p<0.05), indicating significance. Artesunate and placebo groups revealed p=0.003 (p<0.05), also indicating significance. The test results of chemphedon trunk shell capsule extract and artesunate groups showed p=0.475 (p<0.05), indicating no significant differences.Conclusion: Placental histopathologic classification on pregnant mice malaria’s model that received antimalarial chemphedon trunk shell capsule extract of 100 mg/kg BW is better than place-bo and equivalent to artesunate of 36.4mg/kg BW.